1996
DOI: 10.1021/ic950830r
|View full text |Cite
|
Sign up to set email alerts
|

13C CP/MAS NMR Studies of Hemoprotein Models with and without an Axial Hindered Base:  13C Shielding Tensors and Comparison with Hemoproteins and X-ray Structural Data

Abstract: 13C cross-polarization magic-angle-spinning (CP/MAS) NMR spectra of several carbonmonoxide (93-99% (13)C enriched) hemoprotein models with 1,2-dimethylimidazole (1,2-diMeIm) and 1-methylimidazole (1-MeIm) as axial ligands are reported. This enables the (13)CO spinning sideband manifold to be measured and hence the principal components of the (13)CO chemical shift tensor to be obtained. Negative polar interactions in the binding pocket of the cap porphyrin model and inhibition of Fe-->CO back-donation result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…To begin with, we first compare these results with the experimental data published previously by ourselves and by others. ,, In these previous studies, the 13 C and 17 O NMR observables for CO in picket fence porphyrin were reported 14,21 in which CO is linear and untilted . For 13 C, at τ = β = 0° the calculated values (converted from the absolute shieldings using a value of 186 ppm for the absolute shielding of tetramethylsilane, ref ) are δ iso = 215 ppm, |δ 22 − δ 11 | = 13 ppm, and |δ 33 − δ 11 | = 446 ppm, to be compared with experimental values for the linear CO in picket fence porphyrin of δ iso = 205 ppm, |δ 22 − δ 11 | = 8 ppm, and |δ 33 − δ 11 | = 457 ppm.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…To begin with, we first compare these results with the experimental data published previously by ourselves and by others. ,, In these previous studies, the 13 C and 17 O NMR observables for CO in picket fence porphyrin were reported 14,21 in which CO is linear and untilted . For 13 C, at τ = β = 0° the calculated values (converted from the absolute shieldings using a value of 186 ppm for the absolute shielding of tetramethylsilane, ref ) are δ iso = 215 ppm, |δ 22 − δ 11 | = 13 ppm, and |δ 33 − δ 11 | = 446 ppm, to be compared with experimental values for the linear CO in picket fence porphyrin of δ iso = 205 ppm, |δ 22 − δ 11 | = 8 ppm, and |δ 33 − δ 11 | = 457 ppm.…”
Section: Resultsmentioning
confidence: 86%
“…However, the known anticorrelation between 13 C and 17 O shifts seen in numerous proteins 14 is not apparent in the calculated results. In addition, the large (∼80 ppm) anisotropies, |δ 22 − δ 11 |, seen in hemoglobin, myoglobin, and some model systems ,, imply tilt angles between 30° and 40°. This translates to an 18 ppm difference in isotropic chemical shift, while the experimental difference between the protein and the picket fence porphyrin (linear) model is only 0.5 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…carbonmonoxy−heme complexes). NMR spectroscopy is one of the most important tools for the investigation of metal carbonyl complexes and clusters, and in the past, there have been several experimental studies of 13 C and 17 O chemical shifts in metal−CO systems in solution, , as well as more limited studies in the solid state. In addition, for 17 O, the 17 O electric field gradient or quadrupole coupling constant has been measured in solution . All of these parameters are expected to be sensitive to structure and bonding, which may vary considerably from one system to another.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of procedures are used to interpret the computational results, based on a breakdown of contributions from various localized or delocalized molecular orbitals or combinations thereof, which allow us to go considerably beyond previous studies in relating the NMR spectroscopic observables to structure and bonding. This should aid considerably in future studies on systems where less structural information is available such as in metalloproteins and their model systems …”
Section: Introductionmentioning
confidence: 99%
“…The electronic nature of the Fe−C−O unit in heme proteins and synthetic model compounds has been the subject of intensive research activities for several decades. There has been considerable interest in investigating structure−activity relationships by using vibrational spectroscopy with particular emphasis to C−O and Fe−C stretching frequencies and Fe−C−O bending deformation. More recently, considerable new information was obtained by the use of 13 C, 17 O, and 57 Fe NMR both in solution and in the solid state. As pointed out by Oldfield and collaborators,11a there are at least fourteen independent NMR parameters that can be used to describe the nature of the Fe−C−O fragment.…”
Section: Introductionmentioning
confidence: 99%